Analisis Upaya Pajak (Tax Effort) Kota Banda Aceh Studi Komperatif Ibukota Provinsi Di Pulau Sumatera Tahun 2015-2019 - Ferry Setiawan (Program Studi Ekonomi Islam, Fakultas Ekonomi dan Bisnis - Universitas Syiah Kuala, 2022)
The purpose of this study was to determine the Position of Regional Income of Banda Aceh City and analyze the collection effort by comparing it with the provincial capital on the island of Sumatra. This research is limited to an analysis of efforts to collect Regional Income, growth and the role of Regional Income in regional expenditures and the extent to which regional economic developments can encourage an increase in Regional Income in Banda Aceh City. The parameter used is the calculation of Regional Income effort by looking at the Regional Income performance index and the elasticity level of Regional Income, Share and Growth Regional Income, as well as mapping regional financial capabilities.The results of this study conclude that: Banda Aceh City's Regional Income effort is higher than the average for all provincial capitals in Sumatera, The role (share) of Regional Income on government spending in Banda Aceh City was an average of 20.31 percent, the average Regional Income growth of Banda Aceh City was 0.04 percent; the position of Banda Aceh City is in the fourth quadrant with share and growth percentages below the average for all districts/cities in Aceh Province.